Calcium is Necessary for Motility in the Diatom Amphora coffeaeformis - Cooksey, Barbara (1980)
The marine diatom Amphora coffeaeformis required Ca(2+) and bicarbonate for motility. Movement was inhibited by the Ca(2+)-blocking agents ruthenium red and α-isopropyl-α-[(N-methyl-N-homoveratryl)-α- aminopropyl]-3,4,5-trimethoxy phenyl acetonitrile and the metabolic energy uncoupler, carbonyl cyanide 3-chlorophenylhydrazone. 3-(3′,4-Dichlorophenyl)-1,1-Dimethyl urea was without effect on cells at a concentration that prevented O(2) production in the light. Although Sr(2+) could replace Ca(2+) in the attachment of cells to glass, it did not substitute for Ca(2+) in motility.